2018
DOI: 10.1111/epp.12451
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Diaporthe spp. on two blueberry cultivars (Vaccinium corymbosum)

Abstract: Diaporthe vaccinii causes twig blight and fruit rot and is currently listed as a quarantine organism for the European Union. In the Netherlands, two species from the same genus, Diaporthe eres and Diaporthe rudis, are regularly isolated from blighted twigs of Vaccinium corymbosum. This study compared the pathogenicity of these two species to D. vaccinii. To develop a pathogenicity test a field experiment was performed at an experimental station, testing isolates of D. rudis and D. eres. Most of the isolates te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Recognizing it as a synonym of D. eres means that its status as a major pathogen of blueberry would need to be reassessed. Previous studies [ 82 ] have suggested that D. vaccinii is probably not a major threat to blueberry production in Europe and that its status as a quarantine organism should be reappraised.…”
Section: Discussionmentioning
confidence: 99%
“…Recognizing it as a synonym of D. eres means that its status as a major pathogen of blueberry would need to be reassessed. Previous studies [ 82 ] have suggested that D. vaccinii is probably not a major threat to blueberry production in Europe and that its status as a quarantine organism should be reappraised.…”
Section: Discussionmentioning
confidence: 99%
“…Traverso) was recovered from a hemp stem canker located near a blueberry field. These Diaporthe species are reported to infect a broad range of host plants, including blueberry (Lombard et al 2014;Cardinaals et al 2018), apple (Ali et al 2020), blackberry (Vrandecic et al 2011), grapevine (Baumgartner et al 2013;Lawrence et al 2015;Manawasinghe et al 2019), peach (Thomidis and Michailides 2009), pear (Bai et al 2015), plantago (Gomes et al 2013), spruce trees (Sakalidis et al 2021) and cranberry (Michalecka et al 2017). They are considered to be opportunistic pathogens causing root and fruit rots, dieback, cankers, leaf spots, blights, decay and wilt and also occur in plants as endophytes (Udayanga et al 2011(Udayanga et al , 2014Gomes et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although production initiated intensively only in 2011 with a yield of 700 tons and a cultivated area of 75 ha, in 2019 the country was ranked as the 9th largest producer worldwide [5], with a production of 15,418 tons, occupying a total area of 2490 ha [6], making it a highly profitable crop to the economy of the country. However, due to the spread of blueberry plant material across continents, it is expected that several fungal pathogens may affect blueberry orchards, given their entry into new habitats [7]. Some of these pathogens, such as members of Botryosphaeriaceae, Pestalotiopsis sensu lato and Diaporthe can cause twig blight, stem cankers and dieback on blueberry plants [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Members of this genus were previously found to colonize blueberry tissues as latent pathogens or endophytes [8] and as pathogens causing numerous diseases on this crop such as apical necrosis of twigs and stems, cankers, necrosis of the vascular tissues, wilting of leaves, and leaf spots [7,17,18]. These symptoms have been associated with an assemblage of species comprising D. ambigua, D. amygdali, D. australafricana, D. baccae, D. crousii, D. eres, D. foeniculina, D. oxe, D. passiflorae, D. phillipsii, D. rossmaniae, D. rudis, and D. vaccinii (syn.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation